2019
DOI: 10.3390/ma12193091
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Tool Wear Using Artificial Neural Networks during Turning of Hardened Steel

Abstract: The ability to effectively predict tool wear during machining is an extremely important part of diagnostics that results in changing the tool at the relevant time. Effective assessment of the rate of tool wear increases the efficiency of the process and makes it possible to replace the tool before catastrophic wear occurs. In this context, the value of the effectiveness of predicting tool wear during turning of hardened steel using artificial neural networks, multilayer perceptron (MLP), was checked. Cutting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 14 publications
(14 reference statements)
0
31
0
Order By: Relevance
“…The literature survey and our experience obtained during the creation of neural models allowed to identify several characteristic stages occurring during this process [20,25,37,[39][40][41][42]44,45,52]. The creation of an ANN model proceeds in five stages:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature survey and our experience obtained during the creation of neural models allowed to identify several characteristic stages occurring during this process [20,25,37,[39][40][41][42]44,45,52]. The creation of an ANN model proceeds in five stages:…”
Section: Methodsmentioning
confidence: 99%
“…The validation using neural networks gave better results than the one using regression models. The developed forecasting system was able to accurately predict surface wear and roughness [52]. In the fault prognosis context, ANNs are important tools as they enable the implementation of the prediction task easily and accurately [37].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that teaching-learning-based optimization (TLBO) was found to be superior to the bacteria foraging optimization (BFO) in terms of better convergence and a shorter time of computation-hence, the TLBO is recommended during the optimization of hard turning processes. The hardened steel optimization problems were also investigated by Twardowski and Wiciak-Pikuła [11]. They predicted the tool wear during turning of hardened 100Cr6 steel with the application of multilayer perceptron (MLP)-based artificial neural networks.…”
Section: Ofmentioning
confidence: 99%
“…They are based on calibration procedures. This involves process parameters measurement that correlate with wear (cutting force, vibration, sound, acoustic emission, temperature, energy consumption, or surface roughness) [16]. They are easy-to-apply methods, but their reliability is limited regarding direct methods [17].…”
Section: Introductionmentioning
confidence: 99%